Politics of persuasive narrative: legitimizing American invasion of Afghanistan in Khaled Hosseini’s The Kite Runner from a neo-orientalist perspective (IIUC Studies, 2026)
The Kite Runner (2003), published shortly after the American invasion of Afghanistan, has received overwhelming readership in the West and continues to draw critical analysis for its calculated appropriation of Afghan culture tailored for Western audiences. The paper explores Hosseini’s strategies of appropriation, often referred to as the “politics of persuasive narrative”, through which he presents to Western readers the social, cultural, historical, and religious contexts of Afghanistan. Using neo-Orientalism as the theoretical framework, the paper examines how Hosseini employs the politics of persuasive narrative in the novel and finds that his narrative authority and authenticity as the native Afghan author are constructed and feigned, and his history is omissive, distorted and purposively crafted to import Western human rights and introduce secular ideals in the traditional Afghan society. The paper finally concludes that Hosseini’s persuasive politics in the novel is designed to legitimize the American invasion of Afghanistan.IIUC Studies, Vol.-21, Issue-1, Dec. 2024, pp. 117-130